PERAN ISTRI SEBAGAI PENCARI NAFKAH UTAMA DALAM PERSPEKTIF MAQASHID AL-SYARI’AH : (Studi Kasus di Cinere Depok) - Hendro Risbyantoro; Fitri Mutiah Salsa Bela; Delfa Firdaus (Universitas Darunnajah Jakarta, Indonesia, 2023)
In principle, household responsibilities are inseparable from the rights and obligations of each individual. Husbands have a duty to provide for the family's livelihood, while wives have the responsibility of managing the household to the best of their ability. In the Cinere subdistrict of Depok, there are several families in which the wife serves as the primary breadwinner, either because her husband is ill, has been laid off, or is unable to sufficiently meet the family's needs. This research utilizes a qualitative method, specifically a case study research approach (field research), which generates descriptive analytical data in which the author describes the reality of families where the wife is the primary breadwinner, supported by primary and secondary data sources. Data collection techniques included observation, interviews, and documentation with four research subjects whose wives played the role of primary breadwinners. The results of this research indicate that from the perspective of Maqashid Al-Syari'ah, the role of the wife as the primary breadwinner is crucial in preventing harm, ensuring the family's survival, and safeguarding basic interests (maqashid) such as religion, life, intellect, lineage, and property. From an Islamic legal standpoint, there is no prohibition on wives working to earn a living as long as it does not contradict Islamic Sharia